Effect of cutting speed and feed rate on surface roughness of AISI 316l SS using end-milling - Yasir, M. (Asian Research Publishing Network, 2016)
This paper investigates the effect of cutting parameters on the surface topography of AISI 316L stainless steel with tungsten carbide tool by using response surface methodology (RSM). Feed rates ranges from 0.10 mm/rev to 0.14 mm/rev while the cutting speeds ranges from 80 m/min to 120 m/min were used. Scanning electron microscope (SEM) and Mitutoyo surface tester were used to study in detail the surface topography of AISI 316L stainless steel. A mathematical relationship was built between cutting parameters and surface roughness. From the results it was found that feed rate was the main factor affecting the surface roughness while cutting speed have negligible effect on the surface roughness of the end-milled AISI 316L stainless steel samples. From analysis of variance it was found that the percentage contribution of feed rate was 10.38 and cutting speed as 2.1 . Â© 2006-2016 Asian Research Publishing Network (ARPN).